Do we interpret ambiguity and feel according to how we define ourselves? Relationships between self-perception, interpretation biases, and their role on emotional symptoms - Martin-Garcia, Oscar; Blanco, Ivan; Sanchez-Lopez, Alvaro (Frontiers in Psychiatry, 2024)
IntroductionIn today's fast-paced world, depression and anxiety are the most prevalent health problems, generating high economic and social burdens. Interpretation biases seem to play a pivotal role in this emotional problems, influencing how individuals interpret emotionally ambiguous information. These interpretation biases can emerge due to the activation of latent schemas related to how individuals perceive themselves. Therefore, integrating the study of cognitive and self-discrepancy models can offer a comprehensive approach to better understanding the onset or maintenance of emotional symptoms, through their relationship with interpretation biases. In this paper, we aimed to test whether differences in self-perception might act like a cognitive schema that activate cognitive bias, influencing information processing and predicting emotional symptoms.MethodSeventy-three undergraduates completed two different experimental tasks, evaluating self-discrepancies and self-referential negative interpretation bias. Moreover, emotional symptoms were collected after completing the tasks and 1-2 months after, prior to coping with a natural stressor (exam period). The main analyses comprised mediational models, both cross-sectional and longitudinal, with the aim to test whether interpretation bias might act like a mediator in the relation between self-discrepancies and emotional symptoms.ResultsFirst, the results showed significant correlations between higher levels of self-discrepancies (actual-ideal and actual-ought) and higher levels of emotional symptoms (depression and anxiety), as well as with higher negative interpretation biases. Further, cross-sectional mediational models showed that negative interpretation biases partially mediated the relationship between self-discrepancies and emotional symptoms. As for the longitudinal mediation analysis, interpretation bias only mediated the specific relation between actual-ideal self-discrepancies and increases in anxiety symptoms, while the rest of the indirect effects were not significant.DiscussionThese results suggest that self-discrepancies could be understood as indices of the activation of latent cognitive schemas, which would influence subsequent stages of information processing, such as negative interpretations of ambiguous information, partly accounting for the emergence and/or maintenance of emotional symptoms.